Pendidikan Dalam Perspektif Pendidikan Bermutu - Natsir B. Kotten (Ekspektasi: Jurnal Pendidikan Ekonomi, 2016)
In this article the principles of Quality Education have been stated. Only by implementing these principles can quality education be achieved. That is what every educational institution, both public and private must aim for and strive for. The thougts presented by the athor are based mainly on the author’s experiences as a teacher/lecturer for approximately 35 years. In addition, the thoughts of experts and various literatures, especially about the philosophy of quality, are also used by the author to strengthen those thoughts. Hopefuly the contents of this article are useful especially for the glory of society, especially for the benefit of qualified teachers or lectures in the future.